IMPLEMENTATION AND OPTIMIZATION OF THE INDEPENDENT LEARNING CURRICULUM AT SMA NEGERI 11 PANGKEP - Saleh, Muhammad Iqbal; Sangkala, Masnawaty (Universitas Labuhanbatu, 2024)
This study aims to analyze the Implementation and Optimization of the Independent Learning Curriculum at SMA Negeri 11 Pangkep. The variables in this study use the implementation and optimization of the independent curriculum. The population in this study were all teaching staff at SMA Negeri 11 Pangkep. The sampling technique used Purposive sampling. The data collection techniques used were documentation and interviews. The analysis technique used data triangulation. The results of this study are that the implementation of USBN as a school assessment has been implemented based on established regulations and continues to develop following the development of learning. In addition, the AKM and Character Survey methods have been implemented as a replacement for the UN method to be able to determine the academic abilities of students who will continue their education to a higher level. In addition, the use of RPP has been carried out effectively and efficiently and is arranged more concisely based on the development and characteristics of students. Implementation of the four main policies of Merdeka Belajar in the Implementation and Optimization of the Merdeka Curriculum at SMA Negeri 11 Pangkep through the results of observations of the school environment and interviews with the head of the UPT, vice principal of curriculum and class teachers, the implementation and optimization of the Merdeka Curriculum based on the implementation of the four main policies of Merdeka Belajar have been implemented well.Keywords: Implementation, Optimization, Independent Curriculum. Abstrak Penelitian ini bertujuan untuk menganalisis Implementasi dam Optimalisasi Kurikulum Merdeka Belajar Pada SMA Negeri 11 Pangkep. Variabel dalam Penelitian ini menggunakan implementasi dan optimalisasi kurikulum merdeka. Populasi dalam penelitian ini adalah seluruh tenaga pengajar SMA Negeri 11 Pangkep. Teknik pengambilan sampel menggunakan Purposive sampling. Teknik pengumpulan data yang digunakan adalah dokumentasi dan wawancara. Teknik analisis menggunakan trianggulasi data. Hasil penelitian ini adalah bahwa pelaksanaan USBN sebagai asesmen sekolah telah diterapkan berdasarkan peraturan yang telah ditetapkan serta terus berkembang mengikuti perkembangan pembelajaran. Selain itu, metode AKM dan Survey Karakter telah diberlakukan sebagai pengganti metode UN untuk dapat menentukan kemampuan akademik siswa yang akan melanjutkan pendidikannya ke jenjang yang lebih tinggi. Selain itu, penggunaan RPP telah dilakukan secara efektif dan efisien serta disusun dengan lebih ringkas berdasarkan perkembangan dan karakteristik peserta didik. Penerapan empat pokok kebijakan Merdeka belajar dalam Implementasi dan Optimalisasi Kurikulum Merdeka di SMA Negeri 11 Pangkep melalui hasil observasi lingkungan sekolah dan wawancara dengan pihak kepala UPT, wakasek kurikulum dan guru kelas, implementasi dan optimalisasi Kurikulum Merdeka berdasarkan penerapan empat pokok kebijakan Merdeka Belajar telah diterapkan dengan baikKata Kunci: Implementasi, Optimilasi, Kurikulum Merdeka.